Life in pixels : an autobiographical work in progress - Ng, Beverley Jia Hui (2016)
life in pixels: an autobiographical work-in-progress is an ongoing research about my art practice and how I have lived my own life so closely with this process. Inspired by the literary genre of the bildungsroman, this project is a narration of my own coming-of-age. My journals and blog are used as source materials for me to look at how the act of diary keeping have influenced my art practice and communication. Instead of highlighting or concealing the personal issues that drive me to write intensively. It is my intention as a visual communication undergraduate to further develop my own graphic design practice by encompassing art and technology. I also hope to expand on the contemporary self-portrait in this information-driven age.